ANALISIS URGENSI IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY - Rissa Marina Widodo (IQTISHADIA, 2014)
Tulisan ini menganalisi tentang implementasi  Corporate Social Responsibility   di  perusahaan    sebagai   bentuk keikutsertaan perusahaan dalam program pembangunan ekonomi. Untuk menstimulasi perkembangan CSR dalam perkembangan ekonomi yang  berkelanjutan,  diperlukan   model  penerapan  CSR yang efektif, sumber daya manusia dan perusahaan yang berkompeten, peraturan yang tepat dan etika bisnis  serta  dukungan   dari masyarakat untuk menjaga agar penerapan CSR sesuai dengan tujuan yang  diharapkan  dan nilai-nilai   sosial. Keberlanjutan program CSR terbukti  sebagai alternative program untuk memeprkuat masyarakat dan menyelesaikan permaslahan sosial. Sinergitas antara perusahaan, masyarakat dan pemerintah akan menentukan keberhasilan proram yang berkelanjutan.Kata Kunci: CSR , Perusahaan, Pembangunan BerkelanjutanANALYSIS OF THE URGENCY OF CORPORATE SOSIAL RESPONSIBILITY. This article analyzes about the implementation of Corporate  Social Responsibility (CSR) as a commitment of company or business to contribute in the sustainability economic development  program. To stimulate the growth of CSR capably throw in to the sustainability of economic development, it is essential to have an effective CSR model, competent  human resources and institutions, proficient regulation and code of ethics in business, as well as support from public sector to assure the implementation of CSR in line with the goals and the society value. The sustainability of CSR program  is deliberated  to be an alternative for society empowerment to solve social problems and environments that more and more complicated in the last decades. The synergy of business, society, and government  to constantly construct and develop a good quality  society life and environment  will determine  the success of sustainable development program.Keywords: Corporate Social Responsibility, Company, Sustainable Development